ANALISIS MANAJEMEN DAKWAH PERSPEKTIF WALISONGO DALAM PENYEBARAN ISLAM DI TANAH JAWA - M Khusni Mubarok; Lilis Ermawati; Nabilah Maulidah Aliyyah; M Afifuddin; M Anang Sholikhudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to explore the Walisongo's method of managing Islamic propagation in Java. The issues raised in this study are rooted in the Walisongo's success in spreading Islamic teachings with a peaceful, adaptable approach, and attention to local culture in a Javanese society still steeped in Hindu-Buddhist traditions. The method used in this study is a qualitative literature study approach, involving the discussion of various books, scientific journals, and historical sources related to Islamic propagation management and the role of the Walisongo. The findings of this study indicate that the Walisongo's Islamic propagation management was carried out through planning, organizing, implementing, and monitoring functions that are interconnected with the socio-cultural values of Javanese society. The Islamic propagation strategies they implemented included cultural approaches, education, art, tradition, and social role models, so that Islam could be accepted harmoniously without triggering conflict. Furthermore, the Walisongo's Islamic propagation management model is still relevant to current Islamic propagation developments, especially in creating humanistic, tolerant, and contextual communication in a multicultural society. Thus, the Walisongo's perspective on Islamic missionary management can serve as an effective example for the peaceful and sustainable dissemination of Islamic values within society. Keywords: Islamic Missionary Management, Walisongo, Spread of Islam